1‐[2‐(1‐Cyclobutylpiperidin‐4‐yloxy)‐6, 7‐dihydro‐4H‐thiazolo[5, 4‐c]pyridin‐5‐yl]propan‐1‐one: a Histamine H3 Receptor Inverse Agonist with Efficacy in Animal Models of Cognition. (18th November 2021) - Shinde, Anil Karbhari; Badange, Rajesh Kumar; Reballi, Veena; Achanta, Pramod Kumar; Bojja, Kumar; Manchineella, Sravanthi; Rao Muddana, Nageswara; Subramanian, Ramkumar; Choudary Palacharla, Raghava; Benade, Vijay; Jayarajan, Pradeep; Thentu, Jagadeesh Babu; et al.
Abstract: A series of chemical optimizations, which was guided by in vitro affinity at histamine H3 receptor (H3 R), modulation of lipophilicity, ADME properties and preclinical efficacy resulted in the identification of 1‐[2‐(1‐cyclobutylpiperidin‐4‐yloxy)‐6, 7‐dihydro‐4 H ‐thiazolo[5, 4‐ c ]pyridin‐5‐yl]propan‐1‐one (45 e ) as a potent and selective ( K i =4.0 nM) H3 R inverse agonist. Dipsogenia induced by (R)‐α‐methylhistamine was dose dependently antagonized by 45 e, confirming its functional antagonism at H3 R. It is devoid of hERG and phospholipidosis issues. Compound 45 e has adequate oral exposures and favorable half‐life in both rats and dogs. It has demonstrated high receptor occupancy (ED80 =0.22 mg/kg) and robust efficacy in object recognition task and, dose dependently increased acetylcholine levels in brain. The sub‐therapeutic doses of 45 e in combination with donepezil significantly increased acetylcholine levels. The potent affinity, selectivity, in vivo efficacy and drug like properties together with safety, warrant for further development of this molecule for potential treatment of cognitive disorders associated with Alzheimer's disease. Abstract : Pharmacokinetic refinement . The histamine H3 receptor inverse agonist 45 e achieves rapid oral absorption, brain penetration and reduced half lives in rats. It has demonstrated high receptor occupancy and robust efficacy in object recognition task and, dose‐dependently increased acetylcholine levels in brain. The sub‐therapeutic doses of 45 e in combination with donepezil significantly increased acetylcholine levels. These properties warrant for further development of this molecule for potential treatment of cognitive disorders associated with Alzheimer's disease.